How does bonus depreciation affect real investment? Effect size, asset structure, and tax planning - Sebastian Eichfelder; Jonas Knaisch; Kerstin Schneider (Arbeitskreis Quantitative Steuerlehre (arqus), 2023)
We analyze how tax incentives (bonus depreciation) affect real investment choices of firms by exploiting an exogenous variation in regional tax regulation in former East Germany (Development Area Law, DAL). Our rich administrative panel data for the universe of German manufacturing firms at the establishment level allow us not only to identify an aggregate effect, but also to identify which types of investment (equipment, buildings, land) are are most affected (asset structure). Our baseline results suggest that the DAL increased real gross investment by 16.0% to 19.9%. This aggregate effect is primarily driven by additional investments in buildings (76.6% to 92.3%) and land (108.0% to 121.3%) investments, which have the longest regular depreciation periods in absence of bonus depreciation. The impact on equipment investment is significantly smaller (7.3% to 10.5%). Hence, firms did not only increase their real investment, but also adjusted their asset structure in response to the tax incentive. Addressing firm heterogeneity, we observe a stronger response for firms with more than one business establishment and large firms, thereby providing evidence of tax planning opportunities (multi-establishment firms) and relatively low tax planning costs (large firms) enhancing the effect of bonus depreciation on investment. There is only week evidence of financial reporting costs (accounting incentives) moderating the tax induced effect on firms' real investment choices.
Keywords: G11; H25; H32; M41; 330; business taxation; user cost of capital; tax elasticity; real investment